Enhancing Electromechanical Properties of Lead-Free Ferroelectrics With Bilayer Ceramic/Ceramic Composites - Ayrikyan, Azatuhi; Rojas, Virginia; Molina-Luna, Leopoldo; Acosta, Matias; Koruza, Jurij; Webber, Kyle Grant (IEEE Transactions on Ultrasonics Ferroelectrics and Frequency Control, 2015)
The macroscopic electromechanical behavior of lead-free bilayer composites was characterized at room temperature. One layer consisted of a nonergodic relaxor, (Bi1/2Na1/2)TiO3-7BaTiO(3), with an electric-field-induced long-range ferroelectric order, whereas the other is understood to be an ergodic relaxor [(Bi1/2Na1/2)TiO3-25SrTiO(3)] that undergoes a reversible electric-field-induced macroscopic nonpolar-to-polar transition. Microstructural evidence of a bilayer with low diffusion between the two components is also demonstrated. By taking advantage of the different macroscopic strain-and polarization-electric-field responses of the two constituents, internal mechanical and electrical fields can be developed that enhance the unipolar strain over that expected by a rule of mixtures approximation, thereby improving the properties needed for application of such materials to actuator systems. It is possible through further tailoring of the volume fractions and macroscopic properties of the constituents to optimize the electromechanical properties of multilayer lead-free ferroelectrics.